Consumer participation in the credit market during the COVID-19 pandemic and beyond - Evangelos Charalambakis; Federica Teppa; Athanasios Tsiortas (European Central Bank (ECB), 2024)
This paper analyses the consumer's decision to apply for credit and the probability of the credit being accepted in the euro area during a period characterized by the unprecedented concomitance of events and changing borrowing conditions linked to the global COVID-19 pandemic and the Russian invasion of Ukraine. We use data between 2020Q1 and 2023Q2 from the ECB's Consumer Expectations Survey. We find that credit demand is highest when the first lockdown ends and it drops when supportive monetary compensation schemes are implemented. There is evidence that constrained households are significantly less likely to apply for credit. Credit is more likely to be accepted under favourable borrowing conditions and after the approval of national recovery plans. We also find that demographic, economic factors, perceptions and expectations are associated with the demand for credit and the credit grant.
Keywords: C23; D12; D14; G51; 330; Consumer finance; Liquidity constraints; Credit applications; Consumer Expectations Survey